2017
DOI: 10.3389/fphys.2017.00406
|View full text |Cite
|
Sign up to set email alerts
|

Tensiomyographic Markers Are Not Sensitive for Monitoring Muscle Fatigue in Elite Youth Athletes: A Pilot Study

Abstract: Objective: Tensiomyography (TMG) is an indirect measure of a muscle's contractile properties and has the potential as a technique for detecting exercise-induced skeletal muscle fatigue. Therefore, the aim of this study was to assess the sensitivity of tensiomyographic markers to identify reduced muscular performance in elite youth athletes.Methods: Fourteen male junior tennis players (age: 14.9 ± 1.2 years) with an international (International Tennis Federation) ranking position participated in this pre-post s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
32
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 37 publications
(63 reference statements)
5
32
0
1
Order By: Relevance
“…In addition, the training program resulted in an accumulation of OS during the 4-week mesocycle. This is in line with several studies that have demonstrated the exhaustive nature of short-term intensified training cycles ( Billat et al, 1999 ; Halson et al, 2002 ; Wiewelhove et al, 2015 , 2017a ). Interestingly, there was no difference in the increase of OS over time between intervention groups ( Figure 3 ), which is also in agreement with previous research ( Wiewelhove et al, 2016b ) and emphasizes that ACT seems to be neither beneficial nor detrimental to the recovery process.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the training program resulted in an accumulation of OS during the 4-week mesocycle. This is in line with several studies that have demonstrated the exhaustive nature of short-term intensified training cycles ( Billat et al, 1999 ; Halson et al, 2002 ; Wiewelhove et al, 2015 , 2017a ). Interestingly, there was no difference in the increase of OS over time between intervention groups ( Figure 3 ), which is also in agreement with previous research ( Wiewelhove et al, 2016b ) and emphasizes that ACT seems to be neither beneficial nor detrimental to the recovery process.…”
Section: Discussionsupporting
confidence: 92%
“…The present data also show that the Tc for rectus abdominis and triceps brachii was longer than 30ms, indicating they are highly resistant to fatigue and with a high prevalence of slow-twitch fibres [17]. This data may have important implications to design potential muscle-training programs for CPR professionals.…”
Section: Discussionsupporting
confidence: 62%
“…Interestingly, of the seven studies inducing general fatigue, four reported a decrease in Dm, [ 70 , 83 ] two showed an increase in Dm, [ 46 , 82 ] whilst the other showed no change [ 86 ]. It has to be noted though that Raeder et al [ 83 ] Wiewelhove et al [ 70 ] de Paula Simola et al [ 54 ] and de Paula Simola et al [ 69 ] all used variations of high-intensity resistance or endurance training, or interval training, over short periods of time.…”
Section: Applications Of Tensiomyographymentioning
confidence: 99%